A Dual-Factor Releasing Hydrogel for Rotator Cuff Injury Repair - Teng, Chong; Fang, Yifei; Zhu, Huangrong; Huang, Leyi; Jin, Yanglei; Ye, Zhaoming (Frontiers in Materials, 2021)
Rotator cuff injury causes pain in the shoulder and is a challenge to be repaired even after the surgical reconstruction. Here, we developed a dual-factor releasing hydrogel based on sulfhydrylated chitosan to deliver KGN and FGF-2 to the injury part for the fast healing of tendon-bone interface, which is essential for the repair of rotator cuff injury. We found the two factors could be easily loaded into the hydrogel which could in turn continuously release the factors in physiological conditions. The hydrogel was found to be a porous structure through scanning electron microscope (SEM). The micro-pores in the hydrogel structure enable the loading and releasing of these molecules. Besides, in this study, KGN and FGF-2 could play a synergistic effect by recruiting and promoting stem cell proliferation and chondrogenesis, thus accelerating the healing of tendon-bone interface. In vivo study based on rabbit rotator cuff injury model demonstrated that the dual-factor releasing hydrogel possesses superior repair capacity than single-factor releasing hydrogel and the untreated groups. In conclusion, the KGN and FGF-2 dual-factor releasing hydrogel could be a promising biomaterial for the regeneration of tendon-bone interface and rotator cuff injury repair.